Differentiating KMS Strategy from Business Strategy, KM Strategy and IS/IT Strategy - Md. Saad, Nor Hasliza; Alias, Rose Alinda; Abdul Rahman, Azizah (2005)
The era of the new millennium has witnessed a wide range of the revolutionized technology that affects our lives and the way an organization is conducted. The contemporary business sectors start to recognize the potential use of knowledge management in the new organizational processes. As a result, increasing numbers of organizations pay attention to the creative value of leveraging knowledge as one of their potential assets. Therefore, organizations start to focus on knowledge as one of the important elements in competitive advantage that needs to be utilized efficiently and effectively. They have shown a great attention of knowledge management in their business strategy incorporated with technology. The role of technological tools and applications is essential in supporting and enhancing knowledge management strategy. There has been a transition from traditional information system to new a concept of knowledge management system employed by organization to sustain competitive advantage in dynamic and unstable environment. Further, to shift the paradigm of knowledge management systems concept from business sectors, this study focused on the KMS applications and tools particularly in Institutions of Higher Education (IHE) environment. The purpose of this study is to (a) identify the relationship of business strategy, knowledge management (KM) Strategy, knowledge management systems (KMS) strategy, information system (IS) strategy and information technology (IT) strategy, particularly in the context of IHE, (b) describe those strategies and their relationship based on the context of IHE. This will provide guidance and effective methods for formulating the KMS strategy with the aim to align it with business strategies and ensuring success of its implementation.